Study of Band Gap Reduction and Enhanced light Absorption in DSSC’s using N-TiO2 and Azo Dye Composites (International Journal of Scientific Research in Science and Technology, 2024)
This research delves into enhancing Dye-Sensitized Solar Cells (DSSCs) using Nitrogen added Titanium Dioxide (N-TiO2) nanoparticles. Nitrogen is employed to reduce TiO2’s band gap, thereby enhancing its light absorption capabilities. Azo dyes namely VC, RP and RM are chosen as sensitizers due to their efficient light absorption properties. UV-spectrophotometer analysis reveals superior absorption and a lower band gap in N-added TiO2 compared to pure TiO2. Additionally composites of pure TiO2, N-added TiO2 with azo dyes taken in various proportion are explored. Energy band gap of each is calculated using UV- spectrophotometer analysis. Composites made using 8% N and TiO2 with azo dyes VC and RP taken in equal ratio showed the maximum absorption for a range of frequencies from 300nm to 900nm and thus leading to the minimum energy band gap.